The practical impact of indoor temperature on the productivity of prefabricated construction workers using electroencephalogram data - Hao Bai; Yian Lu; Xinying Cao; Shulong Zhuo (Scientific Reports)
Abstract Comprehending the optimal indoor temperature to augment the productivity and cognitive well-being of prefabricated construction workers (PCWs) is essential for enhancing efficiency and safety in construction. Twenty-four workers participated in experiments conducted at indoor temperatures of 24℃, 27℃, 30℃, and 33℃. During the experiments, workers underwent neurobehavioral tests at different indoor temperatures, and thermal sensation and comfort questionnaires were administered post-test to evaluate thermal comfort. Productivity was measured by the accuracy and reaction time in the neurobehavioral tests. Electroencephalogram (EEG) recordings during the tests provided data on attention, mental workload, vigilance, and mental fatigue. The results demonstrate that indoor temperature directly affects workers’ productivity and indirectly impacts it through cognitive states and thermal comfort. Analyzing correlations of cognitive state indicators and their changes over time, 27℃ and 30℃ are more conducive to enhancing PCWs’ productivity. Furthermore, it was observed that workers’ productivity is higher in longer tasks at the same indoor temperature compared to shorter tasks. These results offer practical guidelines for optimizing indoor temperature to better PCWs’ working conditions. By identifying productivity-enhancing temperature ranges, the study provides actionable insights to boost worker efficiency, reduce cognitive strain, and sustain performance.